Contextualizing the Cluster: Palm Oil in Southeast Asia in Global Perspective (1880s–1970s) - Valeria Giacomin (Copenhagen Business School (CBS), 2016)
This dissertation examines the case of the palm oil cluster in Malaysia and Indonesia, today one of the largest agricultural clusters in the world. My analysis focuses on the evolution of the cluster from the 1880s to the 1970s in order to understand how it helped these two countries to integrate into the global economy in both colonial and post-colonial times. The study is based on empirical material drawn from five UK archives and background research using secondary sources, interviews, and archive visits to Malaysia and Singapore. The dissertation comprises three articles, each discussing a major under-researched topic in the cluster literature – the emergence of clusters, their governance and institutional change, and competition between rival cluster locations – through the case of the Southeast Asian palm oil cluster.
hdl:10398/9381
Keywords: 650